Publication trends related to Uses and Gratification Theory on social media - Wibowo, Arif Ardy (International Journal of Communication and Society, 2022)
This analysis aims to analyze publication trends related to the Uses and Gratification Theory and social media in Scopus Journal Articles from 2019-2021. The Uses and Gratification Theory analyzes the genuine social and psychological needs that generate expectations for social media use. Nearly 50 years after, the Uses and Gratification Theory in today’s research is often used in social media. According to the result, most Uses and Gratification Theory articles came from the USA, followed by China, the United Kingdom, Malaysia, and India. Meanwhile, the top five most used keywords are social media (n=130), uses and gratifications (n=68), uses and gratifications theory (n=41), Facebook(n=26), and uses and gratification theory (n=18). To conclude, these number shows the trends of publication related to Uses and Gratification Theory, mostly about social media spanning from 2019-2021. Facebook is the social media most often mentioned, but in the future, Instagram, Twitter, and TikTok, as younger media, could be used as an alternative research object. It also suggested the theme of fake news and its spread, entertainment satisfaction, the rise of mobile entertainment today, and artificial intelligence in media use.